Control of macroscopic characteristics of composite materials for radiation protection - Klepikov, V.F.; Prokhorenko, E.M.; Lytvynenko, V.V.; Zakharchenko, A.A.; Hazhmuradov, M.A. (Вопросы атомной науки и техники, 2015)
Composite materials, intended for radiation protection, were studied. They are made of polystyrene and reinforced by an aluminum. Aluminum is used as a powder. Tungsten powder was added for increase the radiation-protective properties. Examined the state of the composite material at different temperatures. The composite material is dependent on the component. Thermal conductivity of the composite material was studied. It was used in the form of balls and plates. The absorbed dose of gamma-radiation is calculated by mathematical methods. The area where the maximum absorbed gamma quanta found for composites. Изучались композиционные материалы, предназначенные для радиационной защиты. Они базировались на полистироле, который армировался порошковым алюминием. Увеличение радиационно-защитных свойств осуществляли добавлением порошкового вольфрама. Проводилась проверка состояния материалов различного компонентного состава в зависимости от температуры. Изучались характеристики теплопроводности композиционных материалов, выполненных в виде сплошных пластин и шариков. Математическими методами вычислена энергетическая зависимость поглощенной дозы гамма-излучения для полученных образцов. Определялись диапазоны энергий гамма-квантов, при которых применение композиционных материалов наиболее эффективно. Вивчалися композиційні матеріали, призначені для радіаційного захисту. Вони базувалися на полістиролі, який армувався порошковим алюмінієм. Збільшення радіаційно-захисних властивостей здійснювали додаванням порошкового вольфраму. Проводилася перевірка стану матеріалів різного компонентного складу залежно від температури. Вивчалися характеристики теплопровідності композиційних матеріалів, виконаних у вигляді суцільних пластин і кульок. Математичними методами отримана енергетична залежність поглиненої дози гамма-випромінювання для отриманих зразків. Визначалися діапазони енергій гамма-квантів, при яких застосування композиційних матеріалів найбільш ефективне.